Overexpression of abscisic acid-insensitive gene ABI4 from Medicago truncatula, which could interact with ABA2, improved plant cold tolerance mediated by ABA signaling - Li, Yinruizhi; Wang, Mengdi; Guo, Tao; Li, Shuwen; Teng, Ke; Dong, Di; Liu, Zhuocheng; Jia, Chenyan; Chao, Yuehui; Han, Liebao (Frontiers in Plant Science, 2022)
ABI4 is considered an important transcription factor with multiple regulatory functions involved in many biological events. However, its role in abiotic stresses, especially low-temperature-induced stress, is poorly understood. In this study, the MtABI4 gene was derived from M. truncatula, a widely used forage grass. Analysis of subcellular localization indicated that ABI4 was localized in the nucleus. Identification of expression characteristics showed that ABI4 was involved in the regulatory mechanisms of multiple hormones and could be induced by the low temperature. IP-MS assay revealed that MtABI4 protein could interact with xanthoxin dehydrogenase protein(ABA2). The two-hybrid yeast assay and the biomolecular fluorescence complementarity assay further supported this finding. Expression analysis demonstrated that overexpression of MtABI4 induced an increase in ABA2 gene expression both in M. truncatula and Arabidopsis, which in turn increased the ABA level in transgenic plants. In addition, the transgenic lines with the overexpression of MtABI4 exhibited enhanced tolerance to low temperature, including lower malondialdehyde content, electrical conductivity, and cell membrane permeability, compared with the wide-type lines after being cultivated for five days in 4℃. Gene expression and enzyme activities of the antioxidant system assay revealed the increased activities of SOD, CAT, MDHAR, and GR, and higher ASA/DHA ratio and GSH/GSSG ratio in transgenic lines. Additionally, overexpression of ABI4 also induced the expression of members of the ICEs-CBFs-CORs low-temperature response module. In summary, under low-temperature conditions, overexpression of ABI4 could enhance the content of endogenous ABA in plants through interactions with ABA2, which in turn reduced low-temperature damage in plants. This provides a new perspective for further understanding the molecular regulatory mechanism of plant response to low temperature and the improvement of plant cold tolerance.